Modification of Rrmie fiber via impregnation with low viscosity bio-polyurethane resins derived from lignin - Lubis, Muhammad Adly Rahandi; Handika, Sucia Okta; Rita Kartika Sari; Iswanto, Apri Heri; Antov, Petar; Kristak, Lubos; Lee, Seng Hua; Pizzi, Antonio (Multidisciplinary Digital Publishing Institute, 2022)
The purpose of this study was to prepare low-viscosity lignin-based polyurethane (LPU) resins for the modification of ramie (Boehmeria nivea (L.) Gaudich) fiber via impregnation to improve the fiber’s thermal and mechanical properties. Low-viscosity LPU resins were prepared by dissolving lignin in 20% NaOH and then adding polymeric 4,4-methane diphenyl diisocyanate (pMDI, 31% NCO) with a mole ratio of 0.3 NCO/OH. Ramie fiber was impregnated with LPU in a vacuum chamber equipped with a two-stage vacuum pump. Several techniques such as Fourier-transform infrared (FTIR) spectroscopy, differential scanning calorimetry, thermogravimetric analysis, pyrolysis-gas chromatography–mass spectroscopy, field emission-scanning electron microscopy coupled with energy dispersive X-ray (EDX), and a universal testing machine were used to characterize lignin, LPU, and ramie fiber. The LPU resins had low viscosity ranging from 77 to 317 mPa·s−1. According to FTIR and EDX analysis, urethane bonds were formed during the synthesis of LPU resins and after impregnation into ramie fibers. After impregnation, the reaction between the LPU’s urethane group and the hydroxy group of ramie fiber increased thermal stability by an average of 6% and mechanical properties by an average of 100% compared to the untreated ramie fiber. The highest thermal stability and tensile strength were obtained at ramie impregnated with LPU-ethyl acetate for 30 min, with a residual weight of 22% and tensile strength of 648.7 MPa. This study showed that impregnation with LPU resins can enhance the thermal and mechanical properties of fibers and increase their wider industrial utilization in value-added applications.